Attitudes, perceptions and barriers around evidence-based practice in sports physiotherapy in Kenya - Thomas K. Mwololo; Benita Oliver; Wallace M. Karuguti; Joseph M. Matheri (AOSIS, 2021)
Background: Healthcare practitioners are required to integrate clinical experience with the best research evidence for the benefit of the patient. Objective: Determine the attitudes, perceptions and barriers regarding evidence-based practice (EBP) in sports physiotherapy in Kenya. Method: A quantitative crosssectional study was conducted among licensed physiotherapists in the Republic of Kenya through a self-administered questionnaire. Associations between selected sociodemographic characteristics (gender, age, training, experience, specialisation) and attitudes, perceptions and barriers were determined using a Chi-square test. Results: A 55.9% (n = 391) response rate was recorded. A positive attitude towards EBP was reported by 94.6% (n = 370) of the respondents. The most obvious areas of agreement with attitude-and perception-related statements were that 'EBP is important in that patients can receive the best possible treatment' (95.9%; n = 375), and that it is important that 'evidence-based guidelines related to work exist' (84.6%; n = 331). There were no significant associations between the demographic characteristics (gender p = 0.104 [X2 = 2.638;1]; age p = 0.495 [X2 = 2.393;3]; training p = 0.590 [X2 = 4.644;6]; experience p = 0.980 [X2 = 0.426;4] and specialisation p = 0.649 [X2= 0.207;1]); and attitudes and perceptions regarding EBP. Insufficient time was highlighted by 57.8% (n = 226) of the respondents as one of the 'most important barriers'. Conclusion: Although physiotherapists presented with strong positive attitudes towards EBP in sports physiotherapy, barriers were identified which could hinder the implementation of EBP in sports physiotherapy. Clinical implications: Barriers to applying EBP in sports physiotherapy may lead to inferior quality of care for athletes while addressing these barriers is crucial.